Microelectrode arrays: application in batch-injection analysis - Fungaro, Denise A. (1999)
The application of microelectrode arrays in electrochemical batch-injection analysis, injection volumes<=100Â [mu]l, has been investigated using a random array of microdisks (RAM) electrode made with carbon fibres. Preliminary batch-injection experiments involving hexacyanoferrate(II) oxidation, using fixed-potential amperometry and cyclic voltammetry, showed the expected lesser dependence on injection flow rate and the steady-state current characteristics of the RAM electrode, compared to results from similar experiments at macroelectrodes. After electrodepositing mercury on the carbon fibre disks, square wave anodic stripping voltammetry of the test of heavy metals zinc, cadmium and lead was carried out by batch-injection analysis. It was found that the accumulation time of the metals influenced the response to a greater extent than at macroelectrodes, that the influence on the injected volume was similar to that at macroelectrodes and the influence of injection flow rate was less. Detection limits are improved at the RAM electrode; sensitivity as a function of normalised electrode area is also enhanced. Experiments in which the RAM electrode was covered by a thin Nafion film before carrying out BIA-SWASV were also performed, and showed similar trends. Although BIA can be performed directly on real samples without added electrolyte, the combination with microelectrodes, which by themselves permit measurements in highly resistive media and fast scan rates, may prove to be very valuable in extreme situations.